Adsorption of Cr(VI) from aqueous solutions by spent activated clay - Weng C.-H.; Sharma Y.C.; Chu S.-H. (My University, 2025)
Adsorption of Cr(VI) onto spent activated clay (SAC), a waste produced from an edible oil refinery company, was investigated for its beneficial use in wastewater treatment. After pressure steam treatment, SAC was used as an adsorbent. The adsorption kinetic data were analyzed and fitted well in a pseudo-first-order equation and the rate of removal was found to speed up with decreasing pH and increasing temperature. Activation energy for the adsorption process was found to be 4.01-5.47 kcal/K mol. The Langmuir adsorption isotherm was used to fit the equilibrium data and the effect of pH, temperature and ionic strength were studied. The maximum adsorption capacities for Cr(VI) ranged from 0.743 to 1.422 mg/g for temperature between 4 and 40 °C under a condition of pH 2.0. The studies conducted show the process of Cr(VI) removal to be spontaneous at high temperature and endothermic in nature. From the waste utilization and environment point of view, the work carried out is important and useful. Results obtained can serve as baseline data for designing a treatment process using this low-cost adsorbent for the treatment of wastewater rich in Cr(VI). © 2007 Elsevier B.V. All rights reserved.